ANALISIS FRAMING PEMBERITAAN TIDAK BERKIBARNYA BENDERA MERAH PUTIH DI UPACARA PENUTUPAN THOMAS CUP 2020 (STUDI KASUS: CNN INDONESIA.COM DAN PIKIRAN RAKYAT. COM) - Prajna, Nabila (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2022)
In this research, researchers used qualitative research methods. Farida Nugrahani (2014:8) defines qualitative research methods as research methods that can be used to explore and understand the meaning that comes from social or humanitarian problems. This study aims to describe the framing of news in the news of the Red and White Flag Not Flying at the Closing Ceremony of the Thomas Cup 2020 after Indonesia won the Thomas Cup 2020 on CNN Indonesia.com and Mind Rakyat.com. In analyzing the news, the researcher uses Robert N. Entman's framing model analysis which focuses on the selection of issues and highlighting aspects. The results of this study indicate that the news presented by CNN Indonesia.com and Pikiran Rakyat.com provides space for information to the Indonesian people so they can find out how the Red and White flag incident was prohibited from flying during the closing ceremony of the Thomas Cup 2020. This happened because LADI did not carry out their duties related to the doping plan test that has been set by WADA, so that Indonesia is framed as a 'victim' for the negligence that occurred. The solution given to this problem is that the relevant parties (Kemenpora, KOI, LADI) can make every effort to be able to take the punishment given by WADA seriously. News conclusions are the result of media construction of a reality.